Offering Fiber-Enriched Foods Increases Fiber Intake in Adults With or Without Cardiometabolic Risk: A Randomized Controlled Trial - Brandl, Beate; Rennekamp, Rachel; Reitmeier, Sandra; Pietrynik, Katarzyna; Dirndorfer, Sebastian; Haller, Dirk; Hofmann, Thomas; Skurk, Thomas; Hauner, Hans (Frontiers in Nutrition, 2022)
Introduction: Previous efforts to increase fiber intake in the general population were disappointing despite growing awareness of the multiple benefits of a high fiber intake. Aim of the study was to investigate the acceptance and consumption of fiber-enriched foods. Methods: 115 Middle-aged healthy individuals with and without elevated waist circumference (> 102 cm in males and > 88 cm in females) were recruited and randomized to an intervention or an age- and sex-matched control group. Subjects assigned to the intervention group were invited to select fiber-enriched foods from a broad portfolio of products to increase fiber intake by 10 g/day. Control subjects could choose items from the same food basket without fiber enrichment. Primary outcome was the increase in dietary fiber intake, secondary outcomes were changes in cardiometabolic risk factors, microbiota composition, food choices and consumer acceptance of the fiber-enriched foods. Results: Compared to baseline, daily fiber intake increased from 22.5±8.0 g/day to 34.0±9.6 g/day after 4 weeks (p<0.001) and to 36.0±8.9 g/day after 12 weeks (p<0.001) in the intervention group, whereas fiber intake remained unchanged in the control group. Participants rated the taste of the food products as pleasant without group differences. In both groups, the most liked foods included popular convenience foods such as pretzel breadstick, pizza salami and pizza vegetarian. After 12 weeks of intervention, there were minor improvements in plasma lipids and parameters of glucose metabolism in both the intervention and control group compared to baseline, but no differences between the two groups. Increased fiber consumption resulted in an increased (p<0.001) relative abundance of Tannerellaceae. Conclusions: Fiber-enrichment of popular foods increases fiber intake in a middle-aged population with and without cardiometabolic risk and may provide a simple, novel strategy to increase fiber intake in the population. Trial registration: DRKS, DRKS00013058, Registered on 27 September 2017, https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00013058